A Stochastic Predator-Prey System with Stage Structure for Predator - Shufen Zhao; Minghui Song (Abstract and Applied Analysis)
The authors introduce stochasticity into a predator-prey system with Beddington-DeAngelis functional response and stage structure for predator. We present the global existence and positivity of the solution and give sufficient conditions for the global stability in probability of the system. Numerical simulations are introduced to support the main theoretical results.